Caracterización de las deficiencias del lenguaje en un niño de 8 años de edad con trastorno del espectro autista del Centro de Atención Integral Kraaker de la ciudad de Babahoyo - Villamar Franco, Ingrid Ivett (2022)
Language deficiency is one of the most common characteristics in a child with autism spectrum disorder, it is due to the direct relationship that is maintained in some areas of the brain, this part can be improved with individual language therapies and also by establishing contact with their environment will make him capture external stimuli and then learn and acquire some words through reflection and interaction with children his age. The little eye contact in a game are other characteristics of an ASD child, not responding to another person's call even by name, stereotyped movements, the way of staying alone for the longest time, performing repetitive activities without getting bored, not tolerating schedule changes in established activities, the ASD child does not have control of their emotions even more when an anger occurs, are undoubtedly the characteristics that are mostly reflected in an infant with Autism Spectrum Disorder.